Small-Caliber Grenade Projectile Applicable to Individual Grenade Launchers - Taraszewski, Michal; Ewertowski, Janusz (Defence Science Journal, 2018)
An overview of development of grenade types for individual grenade launcher is presented. Considering historical and current research programs, a new type of projectile is proposed. Results of initial experiment which verifies chosen approach are included herein. It is said, based on obtained results, that showed new design can be applied in different applications without negative impact on combat capabilities – it even increases some crucial criteria. Current study indicates nearly 30 per cent increase of the effective exit velocity, however there is a design space where further investigation and optimisation can provide additional profits.